Analisis Pengaruh Ukuran Perusahaan, Struktur Modal dan Kinerja Keuangan Terhadap Nilai Perusahaan pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2021 - Octavia Dwi Sagita Sari; Hwihanus (Jurnal Ekonomi dan Bisnis Digital, 2022)
The aim of this research is to analyze the influence of company size, capital structure and financial performance on company value in banking companies listed on the Indonesian Stock Exchange in 2019-2021. The population in this study was 47 banking companies listed on the IDX in 2019-2021. The sample consisted of 25 companies. The dependent variable in this research is Company Value as measured by Price Book Value (PBV). The independent variables in this research are company size, Capital Structure as measured by Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER), Financial Performance as measured by Return on Assets (ROA) and Return on Equity (ROE). The analytical method used is multiple linear regression using SPSS version 22. The results of the study show that Company Size, Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), Return on Assets (ROA) and Return on Equity (ROE) do not has a significant influence on Company Value as measured by Price Book Value (PBV).